Factors Affecting The Quality of Life of Diabetes Mellitus Type 2 Patients: Literature Review: Quality of live of Diabetes Mellitus Type 2 - Rifdatun Nurul Huwaidah Hasan Fahmi; Candra Bumi; Christyana Sandra (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Objectives: Patients with type 2 diabetes mellitus (T2DM) had experienced physical and psychological complications that affect their daily life, and contribute to poor the quality of life. This study aims to determine the factors that affect the quality of life of people withT2DM based on the SF-36 questionnaire, to improve the factors that can be changed to improve the quality of life of people with T2DM. Methods: This literature review search from 3 databases used including google scholar, PubMed, and the garuda portal with the year of publication of the article in 2015-2021. Some of the literature states similar factors that affect the quality of life of people with T2DM.. Results: Factors that affect the quality of life of people with T2DM, include age, gender, education, complications, and duration of diabetes. Influence is given aspect or the overall value of quality of life Conclusion: The education factor can be improved with the intervention given by peers, so that they can manage T2DM well, and have an impact on improving the quality of life of T2DM patients.